(untitled) (Applied Biological Research, 2015)
Drought stress affects plant growth in several ways including changes in leaf morphology and physiology. Field experiments were conducted in 2009-2011 at the Department of Plant Breeding and Genetics, PAU, Ludhiana (India) in split-plot designwith three replications to analyze the effect of water stress and varying moisture regimes on leaf traits in identified Indian mustard (Brassica juncea L.) genotypes. Moisture stress adversely affected leaf traits while irrigation modules significantly improved leaf characteristics. Specific leaf weight (SLW) was in-significantly affected by irrigation regimes within the genotypes. Specific leaf area (SLA) and Leaf area ratio (LAR) were greatly influenced by irrigation and their interactions were significant. Water stress was intolerable for leaf area and associated traits like length, perimeter, ratio, SLW, SLA, LAR, leaf weight ratio and leaf shoot ratio recording reduction greater than 10%, except for leaf width. Genotype PLM 2 under moisture stress gave higher seed yield of 2210 kg ha-1 and had low drought susceptible index (DSI 1= 0.048) and high drought tolerant index (DTI 1 = 1.164) while genotype MLM-19 had higher DSI 1 of 2.72; low DTI 1 of 0.854 with least seed yield of 1712 kg ha-1 .